2021
DOI: 10.1007/s10815-021-02204-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of thyroid cancer treatment on assisted reproductive technology outcomes in women with infertility

Abstract: Purpose We investigated the effect of different surgical procedures and radioactive iodine treatment (RAIT) on in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) outcomes and evaluated whether possible risk factors, including age, thyroid-stimulating hormone (TSH) levels, and thyroid antibody positivity, were associated with adverse IVF/ICSI outcomes. Methods This retrospective study included 76 women with infertility who had received thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“… 17 In advanced thyroid cancer stages or worse prognosis, the ART become a suitable option to discuss with due to the need to postpone pregnancy and minimizing age factor on ovarian reserve. 32 , 35 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 17 In advanced thyroid cancer stages or worse prognosis, the ART become a suitable option to discuss with due to the need to postpone pregnancy and minimizing age factor on ovarian reserve. 32 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…17 In advanced thyroid cancer stages or worse prognosis, the ART become a suitable option to discuss with due to the need to postpone pregnancy and minimizing age factor on ovarian reserve. 32,35 Warranting women reproductive and sexual rights 27,37 is among our task after thyroid cancer is diagnosed since there is a clear and direct relation among thyroid hormones, pregnancy, and fetal physiology. We need to raise the awareness and offer the various preserving fertility options as well as transmitting the importance of a normal thyroid function and antibodies profile in order to obtain and maintain pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical data showed that COVID‐19 mRNA vaccines offer protection rates of up to 95% (Pfizer/BioNTech & Moderna) 7,8 and also have high production capacity and a rapid development cycle. Overall, mRNA vaccine technology has significant benefits in terms of controlling outbreaks of infectious diseases 9–11 …”
Section: Figurementioning
confidence: 99%
“…Thyroidectomy and long-term thyroid hormone-suppression therapy could lower the chance of tumor recurrence, but the resulting partial or total reduction in thyroid function may impact female fertility and result in adverse pregnancy outcomes [9]. I-131 therapy is commonly used for remnant ablation and adjuvant therapy [10].…”
Section: Introductionmentioning
confidence: 99%